Answer:
x = - 2
Step-by-step explanation:
(f + g)(x)
= f(x) + g(x)
= x² - 2x + 6x + 4
= x² + 4x + 4
Equating to zero
x² + 4x + 4 = 0
(x + 2)² = 0
x + 2 = 0
x = - 2
Answer:
$86.55
Step-by-step explanation:
8.5% x 95 = 8.455
95 - 8.455 = 86.545 = $86.55
Answer:
258
Step-by-step explanation:
Set up the two equations needed (x is the adult tickets and y is the student tickets)
x+y=372
6x+2y=1776
Solve by elimination
-2(x+y=372)
=-2x-2y=-744
Cancel like figures:
-2x-2y=-744
6x+2y=1776
= 4x=1032
x=258
Answer:
8.54
Step-by-step explanation:
formula:
![d=\sqrt{(x2-x1)^2 + (y2-y1)^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28x2-x1%29%5E2%20%2B%20%28y2-y1%29%5E2%7D)
![d=\sqrt{(-4 - (-7))^2 + (0-(-8))^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28-4%20-%20%28-7%29%29%5E2%20%2B%20%280-%28-8%29%29%5E2%7D)
![d=\sqrt{3^2 + 8^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B3%5E2%20%2B%208%5E2%7D)
![d=\sqrt{9 + 64}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B9%20%2B%2064%7D)
![d=\sqrt{73}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B73%7D)
d= 8.54